Analisis Kelayakan Usaha Industri Tembakau Sebagai Komoditas Unggulan Berorientasi Ekspor dalam Upaya Restrukturisasi Ekonomi Pasca Pandemi - Mahfud Nugroho; Eka Kurnia Patmasari; Septian Dwi Cahyo (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2024)
This study evaluates the investment feasibility of UD Al-Mustofa, a tobacco business in Kendal, by considering aspects of production, storage capacity, waste management, and market expansion opportunities. UD Al-Mustofa is strategically located, ensuring high mobility, optimal production scale, and an effective waste management system, which includes recycling solid waste into organic fertilizer, processing liquid waste, and mitigating gas emissions by conducting tobacco drying in areas far from residential zones. Although the business has not yet obtained certification for international markets, financial analysis indicates that investment in this venture is viable. The calculations show a payback period of 2.01 years, significantly shorter than the projected 10-year investment lifespan. The Net Present Value (NPV) reaches IDR 489,345,567, indicating positive returns, with a profitability index of 0.854. The Internal Rate of Return (IRR) of 46% significantly exceeds Bank Indonesia’s interest rate of 5.75% in 2024, while the Average Rate of Return (ARR) of 78.8% is higher than the cost of capital. Based on these findings, UD Al-Mustofa has strong potential for further development, both in terms of production and market expansion..